Patriotism dilemma among Malaysian youth: Between strategy and reality - Mohamed, Ahmad Shah Pakeer; Sulaiman, Sulhairil Hafiz; Othman, Muhammad Fuad; Che Jumaat Yang, Mohd Ashraf; Haron, Hudrus (Centre for Promoting Ideas, 2011)
Development of the country has been the ultimate agenda since the independence of Malaysia, in year 1957 up to now.The development of the country will inevitably involve the development of the current younger generation who will eventually be taking over the leadership of the country.Here, the generation that needs to be focused upon is the youth, the ones who will be leading the government as well as the country in the future.The youth should not be ignored in the country’s development scheme plan. Therefore, this write up concentrates on the elaboration and suggestions on how to developed patriotic spirit in youth.